Penetration of spectinomycin into cerebrospinal fluid duirng experimental meningitis. - Delgado, D G (1980)
The concentration of spectinomycin in serum and cerebrospinal fluid was compared in rabbits with and without experimental pneumococcal meningitis. When injected intravenously, spectinomycin could not be detected in the cerebrospinal fluid of normal rabbits. In rabbits with meningeal inflammation, however, spectinomycin penetrated the blood-brain barrier and produced significant cerebrospinal fluid concentrations, equal to or well above spectinomycin minimal inhibitory concentrations for many bacterial species.